Temperature-Conductivity Relationship of Solid Polymer Electrolyte Membrane Based on PVA-K2CO3 - Abdulkadir, B.A. (Springer Science and Business Media B.V., 2021)
Solid polymer electrolyte for energy storage devices draws extensive considerations nowadays. In this study, we prepared an eco-friendly, flexible and transparent solid polymer electrolyte (SPE) from biodegradable polymer and conducting salt of the poly vinyl alcohol and potassium carbonate (PVA-K2CO3) by solution casting method. The prepared electrolyte was characterized using Fourier transform infrared (FTIR) for their functional groups and electrochemical impedance spectroscopy (EIS) for their electrochemical properties. The result for characterization shows that, there is formation of composite between polymer and the salt that designates the complete composites formation between polymer and the salts, which formed PVA-K2CO3. The obtained PVA-K2CO3 electrolyte with good flexibility exhibits highest conductivity of 9.4 Ã 10â5 mScmâ1 at 373.15Â K. The outcomes equally show that, the electrolyte in this study is dependent on temperature as ionic conductivity increases with increase in temperature. The good results found in this study showed that, the PVA-K2CO3 as a newly developed SPE has a prospective applications in solid-state and flexible energy storage devices. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.